Cumplimiento de la aplicación de los estándares de calidad en la atención prenatal en el Hospital Teófilo Dávila entre los meses de septiembre del 2010 a marzo del 2011 - Álvarez Maldonado, Magdalena L. (2012)
This is a descriptive study – retrospective, which had intended to determine compliance with the standards of quality in the prenatal care. This study was carried out at the Teófilo Dávila hospital of the city of Machala between the months of September 2010 to March 2011, earning a universe of study of 1215 pregnant women of which the sample of 476 patients was obtained by 7 months of research that met the conditions for inclusion.